Proteoglycans as Therapeutic Targets in Brain Cancer - Yan, Zoya; Wang, Shanzhi (Frontiers in Oncology, 2020)
Proteoglycans (PGs) are heavily glycosylated diverse proteins consisting of a “core protein” covalently attached to glycosaminoglycans (GAGs) and present on the cell surface, extracellular matrix, and intracellular milieu. Extracellular proteoglycans play crucial roles in facilitating cell signaling and migration, interacting with growth factor receptors, intracellular enzymes, extracellular ligands, and matrix components, as well as structural proteins and promoting significant tumor-microenvironment interactions in cancerous settings. As a result of their highly regulated expression patterns, recent research has focused on the role of proteoglycans in the development of nervous tissue, such as their effect on neurite outgrowth, participation in the development of precursor cell types, and regulation of cell behaviors. The present review summarizes current progress for the studies of proteoglycan function in brain cancer and explains recent research involving brain glycoproteins as modulators of migration, cell adhesion, glial tumor invasion, and neurite outgrowth. Furthermore, we highlight the correlations between specific proteoglycan alterations and the suggested cancer-associated proteoglycans as novel biomarkers for therapeutic targets.